2008
DOI: 10.1128/aem.01531-07
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Lactococcus lactis in Coculture with Saccharomyces cerevisiae

Abstract: The study of microbial interactions in mixed cultures remains an important conceptual and methodological challenge for which transcriptome analysis could prove to be the essential method for improving our understanding. However, the use of whole-genome DNA chips is often restricted to the pure culture of the species for which the chips were designed. In this study, massive cross-hybridization was observed between the foreign cDNA and the specific Lactococcus lactis DNA chip. A very simple method is proposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 43 publications
(37 reference statements)
2
32
0
Order By: Relevance
“…1). A recent study deals with the transcriptome analysis of L. lactis grown in milk in coculture with S. cerevisiae (98). Although no difference in growth was observed between the coculture and a L. lactis mono culture, a number of genes were differentially expressed, in particular genes involved in pyrimidine metabolism.…”
Section: Genomics Approaches For Mixed-culture Researchmentioning
confidence: 99%
“…1). A recent study deals with the transcriptome analysis of L. lactis grown in milk in coculture with S. cerevisiae (98). Although no difference in growth was observed between the coculture and a L. lactis mono culture, a number of genes were differentially expressed, in particular genes involved in pyrimidine metabolism.…”
Section: Genomics Approaches For Mixed-culture Researchmentioning
confidence: 99%
“…Indeed, various studies have used "omics" techniques to probe the changes that occur during BFIs at the subcellular level (25,94,167,231,235,259,281,352); for example, a recent study of the arbuscular mycorrhizal fungus Gigaspora margarita using combined proteomic and lipid metabolite profiling revealed that the presence of endobacteria had a significant impact on fungal physiology (331). Targeted approaches assessing the proteomic or transcriptomic responses of one BFI partner to molecules produced by the other also allow the testing of specific hypotheses relating to BFIs, such as responses to antibiotics (245,246).…”
Section: Consequences Of Bacterial-fungal Interactions For Participatmentioning
confidence: 99%
“…In natural conditions, heterotrophic micro-organisms are exposed to fluctuating C i levels, for example in the gastrointestinal tract or fermenting matter (Maligoy et al, 2008), to which they respond by adjusting their metabolism to outcompete neighbouring microflora. One-third of L. plantarum-related strains isolated from natural environments are conditional C i -dependent prototrophs (Bringel & Hubert, 2003), but the molecular basis of this CO 2 requirement has only been partially explained (Bringel et al, 2008).…”
Section: Changing C I Availability Affects Several Metabolic Pathwaysmentioning
confidence: 99%
“…Regulation of gene expression in response to C i concentrations was proposed for genes involved in general stress response or purine metabolism in cyanobacteria (Wang et al, 2004), the cad operon in Escherichia coli (Takayama et al, 1994), uncharacterized genes in Pseudomonas sp. S91 (Stretton et al, 1996) and for pyr genes in two lactic acid bacteria species, L. plantarum and Lactococcus lactis (Arsène-Ploetze et al, 2006a;Maligoy et al, 2008). The L. plantarum de novo pyrimidine biosynthesis operon and pyrP gene that code for the PyrR 1 -B-C-Aa 1 -Ab 1 -D-E-F-P proteins and the uracil permease, involved in preformed pyrimidine rescue, are differently expressed in response to C i availability.…”
Section: Introductionmentioning
confidence: 99%